2013
DOI: 10.1186/1472-6882-13-142
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidant and anticancer properties of the seed extracts of Syzygium fruticosum Roxb. growing in Rajshahi, Bangladesh

Abstract: BackgroundThe use of plants and their derived substances increases day by day for the discovery of therapeutic agents owing to their versatile applications. Current research is directed towards finding naturally-occurring antioxidants having anticancer properties from plant origin since oxidants play a crucial role in developing various human diseases. The present study was designed to investigate the antioxidant and anticancer properties of Sygygium fruticosum (Roxb.) (abbreviated as SF).MethodsThe dried coar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
63
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 35 publications
8
63
1
1
Order By: Relevance
“…As far as all cellular components, proteins, polyunsaturated fatty acids, nucleic acids, and carbohydrates are prominent biological targets of reactive oxygen species, giving rise to metabolic and cellular disturbances. Foods, rich in antioxidants, should play an essential role in the prevention of many pathologies such as cardiovascular diseases, cancer, and neurodegenerative diseases as well as cell inflammatory problems caused by cutaneous agents (Islam et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As far as all cellular components, proteins, polyunsaturated fatty acids, nucleic acids, and carbohydrates are prominent biological targets of reactive oxygen species, giving rise to metabolic and cellular disturbances. Foods, rich in antioxidants, should play an essential role in the prevention of many pathologies such as cardiovascular diseases, cancer, and neurodegenerative diseases as well as cell inflammatory problems caused by cutaneous agents (Islam et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, prevention of oxidative damage caused by ROS is an important strategy for the prevention and treatment of cancer. Plants rich in antioxidative polyphenols have been linked to a decreased risk for developing cancer through various mechanisms, including apoptosis [44, 45]. Thus, intensive efforts have been undertaken to search for plant-derived antioxidants and anti-cancer agents that are both effective and safe [45, 46].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that anticancer property of phenolic compounds is due to their antioxidant activity (Islam et al, 2013;Ghasemzadeh and Jaafar, 2013). Natural phenolics have been found to intervene at all stages of cancer development by their antioxidant action (Dai and Mumper 2010).…”
Section: Discussionmentioning
confidence: 99%